PENGARUH KOMITMEN DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU PADA GUGUS III BALIKPAPAN BARAT - Sri Suhartini; Nugroho Mardi Wibowo; C. Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to find out the description of the teachers of SD III Gugus III West Balikpapan, theleadership style applied and the teacher performance of SDN Gugus III West Balikpapan, to determinethe role and style of leadership simultaneously and partially towards the performance of teachers ofSDN Gugus III West Balikpapan. This study uses a quantitative approach and type of explanatoryresearch. The population in this study were all teachers at SDN Gugus III West Balikpapan. Anexample of this study was aimed at 32 teachers. The sampling technique uses saturated samples. Datacollection methods use questionnaires and documentation. Data analysis methods are descriptive andmultiple regression analysis. The results of this study indicate the teacher's commitment of SDNGugus III West Balikpapan in good category, the leadership style of the principal in the teachers ofSDN Gugus III West Balikpapan is also in good category. Likewise, the performance of the teachers ofSD III Gugus III West Balikpapan is in good category. The proof is that there is a relationship betweenorganizational commitment and leadership style on the performance of teachers at SDN Gugus IIIWest Balikpapan. APPROACH TO HELP PROGRAM FOR USE OF SDN Gugus III WestBalikpapan. Keywords: organizational commitment, leadership style, teacher performance